Is there any financial kuznets curve in Jordan? a structural time series analysis - Ibrahim N. Khatatbeh; Wasfi Al Salamat; Mohammed N. Abu-Alfoul; Jamil J. Jaber (Cogent Economics & Finance)
This paper investigates the notion of the financial Kuznets curve in an emerging country—Jordan. Both variants of the financial Kuznets curve (growth financial Kuznets curve and inequality financial Kuznets curve) have been examined using different time series methodologies applying to a sample period from 1993 to 2017. The unobserved components model results provide evidence for both variants of the financial Kuznets curve when using private credit to GDP as a proxy for financial-sector development. Moreover, non-nested model tests suggest that financial intermediaries are relatively more important than stock markets for income inequality. Overall, this paper provides evidence for the financial Kuznets curve in emerging countries. Moreover, it provides new insights for policymakers in Jordan in their challenge to boost economic growth and decelerate income inequality, by reversing the trend towards the concentration of power in the financial sector and creating public-financial institutions that provide affordable credit to small businesses and households.